Age group DNA methylation differences in lemon sharks (Negaprion brevirostris): Implications for future age estimation tools. Issue 8 (29th August 2022) - Beal, Andria Paige; Hackerott, Serena; Feldheim, Kevin; Gruber, Samuel H.; Eirin‐Lopez, Jose M.
Abstract: Age information is often non‐existent for most shark populations due to a lack of measurable physiological and morphological traits that can be used to estimate age. Recently, epigenetic clocks have been found to accurately estimate age for mammals, birds, and fish. However, since these clocks rely, among other things, on the availability of reference genomes, their application is hampered in non‐traditional model organisms lacking such molecular resources. The technique known as Methyl‐Sensitive Amplified Polymorphism (MSAP) has emerged as a valid alternative for studying DNA methylation biomarkers when reference genome information is missing, and large numbers of samples need to be processed. Accordingly, the MSAP technique was used in the present study to characterize global DNA methylation patterns in lemon sharks from three different age groups (juveniles, subadults, and adults). The obtained results reveal that, while MSAP analyses lack enough resolution as a standalone approach to infer age in these organisms, the global DNA methylation patterns observed using this technique displayed significant differences between age groups. Overall, these results confer that DNA methylation does change with age in sharks like what has been seen for other vertebrates and that MSAP could be useful as part of an epigenetics pipeline to infer the broad range of ages found in large samples sizes. Abstract : Epigenetic clocks have been found to accurately estimate age for several species, however, these clocks rely heavily on the availability of reference genomes. This study explores the potential for using MSAP as an alternative to higher throughput methods for the analysis of age in sharks. Our results indicate that MSAP could be useful as part of an epigenetics pipeline to infer broad age ranges.